2016
DOI: 10.1021/acs.jpcc.6b10778
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dopant Addition on Lattice and Luminescence Intensity Parameters of Eu(III)-Doped Lanthanum Orthovanadate

Abstract: A series of La 1−x Eu x VO 4 samples with a different Eu 3+ content was synthesized via a hydrothermal route. An increase in the dopant content resulted in a decrease in lattice constants of the materials. Plane-wave DFT calculations with PBE functional in CASTEP confirmed this trend. Next, CASTEP calculations were used to obtain force constants of Eu−O bond stretching, using a novel approach which involved displacement of the Eu 3+ ion. The force constants were then used to calculate charge donation factors g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…On the basis of recent theoretical considerations, the Ω 2 intensity parameter is by far mostly influenced by small angular changes in the local coordination geometry,,, while Ω 4 and mainly Ω 6 are by far the most sensitive to lanthanide‐ligating atom bond distances and, therefore, to covalency . This fact together with changes in the ligating atoms polarizabilities (α) have been used to rationalize the hypersensitive character of certain 4 f intraconfigurational transitions to changes in the chemical environment.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of recent theoretical considerations, the Ω 2 intensity parameter is by far mostly influenced by small angular changes in the local coordination geometry,,, while Ω 4 and mainly Ω 6 are by far the most sensitive to lanthanide‐ligating atom bond distances and, therefore, to covalency . This fact together with changes in the ligating atoms polarizabilities (α) have been used to rationalize the hypersensitive character of certain 4 f intraconfigurational transitions to changes in the chemical environment.…”
Section: Resultsmentioning
confidence: 99%
“…A great number of optically active functional materials is based on the Ln 2+/3+ , because of their unique spectroscopic properties, such as multicolor photoluminescence induced by UV or near‐infrared (NIR) (energy up‐conversion) irradiation, narrow absorption/emission bands, large spectral shift of the emission bands in relation to the absorption ones, long emission lifetimes, etc . Matrices hosting Ln 3+ ions are usually fluorides, oxides, vanadates, phosphates, and borates .…”
Section: Introductionmentioning
confidence: 99%
“…The 320 nm band in vanadate compounds is usually connected with 1 A 1 → 1 T 2 transitions in the VO 4 3‐ anions . The additional wide excitation band near 370–390 nm is related with influence of the Ca 2+ impurities as this band was not observed nor for the EuVO 4 neither for the Ca‐free La 1− x Eu x VO 4 samples (Figure , curve 5,). Origin of this band will be considered below when discussing emission spectra in their comparison with properties of the La 1− x − y Eu y Ca x VO 4 compounds.…”
Section: Luminescent Propertiesmentioning
confidence: 96%
“…Previous investigations have shown that partial replacements of the RE cations with iso‐ and heterovalent ions in the REVO 4 compounds lead to various changes of their physical and chemical characteristics . In particular, replacement of the RE cations with alkaline earth (AE) cations (Ca 2+ , Sr 2+ , Ba 2+ ) in the RE vanadate nanoparticles causes increase of luminescent intensity and arising of additional excitation band in violet spectral range of light …”
Section: Introductionmentioning
confidence: 99%